The influence of digital marketing on purchase intention for the dior brand in indonesia - Stephanie Regina; Margaretha Pink Berlianto (Enrichment : Journal of Management, 2022)
The digital world is growing, especially in digital marketing or social media. Thus, many brands immediately decide to explore social media and develop digital marketing strategies, the efficiency of which is tracked to increase improvement. This study aims to understand the influence of social media marketing, consumer attitude, nature of the message, brand equity, perceived social value, utilitarian value, and economic value on purchase intention of the Dior brand in Indonesia. This research is causal research using a descriptive quantitative approach. The population used in this study were people who had never shopped at Dior in Indonesia, while the sample taken was 240 people. This research is sourced from primary data obtained through questionnaires. The data analysis technique used in this research is Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS) program. The results of this study indicate that brand equity and economic value positively affect purchase intention. Meanwhile, social media marketing, customer attitude, nature of the message, perceived social value, and utilitarian value do not affect purchase intention. The contribution of this research is expected to be a consideration and input for the Dior brand in Indonesia to increase the factors that influence purchase intention on the Dior brand.